(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Describing the current state of hearing loss and describing the distribution of some related factors of 2-5 years old children at 4 kindergartens in Ly Nhan district, Ha Nam province in 2019. Subject and methods: A cross-sectional study was conducted among children aged 2–5 at 4 kindergartens in Ha Nam Province, Vietnam. The investigator measured the OAE according to the standard procedure at the preschool. Children who have negative OAE test results for the first time will have their second cochlear stimulation test (2nd OAE) and have a physical examination at Vietnam National Hospital of Paediatrics. Directly interview the mother of the children participating in the study to collect information about related factors. Results: The rate of children with hearing loss at the age of 2-5 years old was 0.0566, of which transmission causes accounted for 71.84%, receptive causes accounted for 11.65% and mixed causes accounted for 16.51%. The rate of mild – moderate – severe hearing loss is 67.96% - 17.48% - 14.56%. Among children with hearing loss, 62.14% of children had otitis media, 11.65% of children had ear surgery, 6.8% of children had been hospitalized in the ICU for more than 5 days, 3.88% of children ever had kernicterus, 3.88% of children had a family history of hearing loss, 1.94% of children had encephalitis, 1.94% of children were born prematurely, and 0.97% of children had sudden deafness. Conclusion: The rate of hearing loss at the age 2-5 years old at 4 kindergartens in Ha Nam province is 0,566. Some factors, such as nuclear jaundice, chronic otitis media, post ear surgery, and maternal infectious disease during pregnancy, were associated with hearing loss at 4 kindergartens in Ha Nam province. Children with these factors should have an OAE test to detect hearing loss early.